Categorisation of Lubukusu conceptual metaphors of pain in doctor-patient consultation - Wanjala, Wakoko Makarios; Mudogo, Benard Angatia; M’raiji, John Kirimi (Research Journal in Advanced Humanities, 2022)
This study examines the metaphors of pain embedded in the conceptual systems of Lubukusu speakers and seeks to establish how categories of these metaphors becomes significant for adequate understanding of emotional reality. The study adopted analytical research design. Nurses were engaged in a role-play of doctor-patient consultations in Lubukusu to bring out a reflection of their experiences with terminally ill Bukusu patients in their medical care. The source domain for the categories of the metaphors analysed to map the source domain are; PLANT, ANIMAL, BAD SMELL, BAD TASTE, SUPERNATURAL, NON-LIVING and MIXED CAUSE onto the target domains of pain. Although there is a lot of research on emotion metaphors, much still remain unknown especially as pertains to the knowledge of corporeal experiences in the conceptualisation of pain. In this view, the paper explores the role of these experiences in the structuring of Lubukusu speaking patients’ concepts of pain when seeking medical services from non-native Lubukusu Doctors. The study sheds light on the need for stakeholders in the health sector to engage linguists in addressing the glaring mismatches, miscommunication and misunderstandings in health communication.